Spottier Targets Are Less Attractive to Tabanid Flies: On the Tabanid-Repellency of Spotty Fur Patterns - Blaho, Miklos (Public Library of Science, 2012)
During blood-sucking, female members of the family Tabanidae transmit pathogens of serious diseases and annoy their host animals so strongly that they cannot graze, thus the health of the hosts is drastically reduced. Consequently, a tabanid-resistant coat with appropriate brightness, colour and pattern is advantageous for the host. Spotty coats are widespread among mammals, especially in cattle (Bos primigenius). In field experiments we studied the influence of the size and number of spots on the attractiveness of test surfaces to tabanids that are attracted to linearly polarized light. We measured the reflection-polarization characteristics of living cattle, spotty cattle coats and the used test surfaces. We show here that the smaller and the more numerous the spots, the less attractive the target (host) is to tabanids. We demonstrate that the attractiveness of spotty patterns to tabanids is also reduced if the target exhibits spottiness only in the angle of polarization pattern, while being homogeneous grey with a constant high degree of polarization. Tabanid flies respond strongly to linearly polarized light, and we show that bright and dark parts of cattle coats reflect light with different degrees and angles of polarization that in combination with dark spots on a bright coat surface disrupt the attractiveness to tabanids. This could be one of the possible evolutionary benefits that explains why spotty coat patterns are so widespread in mammals, especially in ungulates, many species of which are tabanid hosts.